Sports-related concussion increases the risk of subsequent injury by about 50% in elite male football players - Nordström, A.; Nordström, P.; Ekstrand, J. (British Journal of Sports Medicine, 2014)
Background: Little is known about the short-term and long-term sequelae of concussion, and about when athletes who have sustained such injuries can safely return to play.